Validitas Instrumen Karakterisasi Kemampuan Metakognisi Mahasiswa Calon Guru Fisika - Asy'ari, Muhammad; Ikhsan, Muhamad; Muhali, Muhali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
The purpose of this study was to describe the validity of the metacognition ability instruments which include metacognition knowledge and metacognition awareness. The metacognition knowledge instrument in the form of essay tests totaling 20 items, while the metacognition awareness instrument is the Metacognition Awareness Inventory (MAI). This study is a descriptive qualitative study to assess and obtain the quality of metacognition knowledge and metacognition awareness instruments that are valid to characterize student metacognition abilities. The instrument of student metacognition knowledge was validated by two physics educations’ experts, the instrument of metacognition knowledge was also empirically validated by involving 30 physics education students as respondents. Unlike the instrument of metacognition knowledge, the metacognition awareness instrument is only empirically validated by involving 90 students across the study program as respondents. The results showed: (1) the validator's assessment of the metacognition knowledge instrument both from the content validity aspect and construct validity was valid categorized (range of scores> 3.6) and reliable for the two components of assessment in a row namely Percentage of agreement = 97.3% and 98.6%, (2) the empirical validity of the metacognition knowledge instrument was declared valid (Pearson Correlation > rtable) and reliable (Cronbach's alpha = 0.944), (3) the instrument of metacognition awareness was declared reliable (0.6 ≤ α ≤ 1.0) although some components of the student metacognition awareness instrument are empirically declared invalid. These results indicate that the instrument of metacognition ability is valid to use in characterizing the prospective physics teacher students’ metacognition ability.